Leptin correlates with monocytes activation and severe condition in COVID-19 patients. Issue 1 (6th January 2021) - Wang, Jingya; Xu, Yinyin; Zhang, Xiaoli; Wang, Sheng; Peng, Ziyi; Guo, Jing; Jiang, Hongmei; Liu, Jing; Xie, Ying; Wang, Jingjing; Li, Xin; Liao, Juan; et al.
Abstract: Excessive monocyte activation with the development of excessive or uncontrolled release of proinflammatory cytokines often results in host tissue injury and even death in patients with pneumonia caused by the 2019 novel coronavirus. However, the changes of cytokine profiles of coronavirus disease 2019 (COVID-19) patients, as well as the underlying mechanisms that are involved, remain unknown. Using a cytokine array containing 174 inflammation-related cytokines, we found significantly altered cytokine profiles in severe COVID-19 patients compared with those in mild patients or healthy controls, and identified leptin, CXCL-10, IL-6, IL-10, IL-12, and TNF-α as the top differentially expressed cytokines. Notably, leptin showed high consistency with CXCL-10 and TNF-α in predicting disease severity, and correlated with body mass index, decreased lymphocyte counts, and disease progression. Further analysis demonstrated that monocytes in severe patients with higher leptin levels were inclined toward M1 polarization. Mechanistic studies revealed that leptin synergistically up-regulated expression levels of inflammatory cytokines and surface markers with IL-6 in monocytes through STAT3 and NF-κB signaling pathways. Collectively, our results suggest that overweight COVID-19 patients were prone to have higher leptin levels, which further activated monocytes, resulting in amplified or dysregulated immune responses. Taken together, our findings argue that leptin correlates severity of COVID-19 and may indicate a possible mechanism by which overweight patients have a greater tendency to develop severe conditions. Graphical Abstract: Leptin correlates severity of COVID-19, providing a possible mechanism whereby overweight cases are prone to develop severe conditions.